Enhanced the mechanical strength of polyimide (PI) nanofiber separator via PAALi binder for lithium ion battery. (April 2021) - Li, Menglin; Sheng, Lei; Xu, Rong; Yang, Yang; Bai, Yaozong; Song, Shangjun; Liu, Gaojun; Wang, Tao; Huang, Xianli; He, Jianping
Abstract: Polyimide (PI) nanofiber membrane prepared by electrospinning technique exhibits poor mechanical strength for the slippage of fibers, which limits it applied into lithium ion battery (LIB). In this study, we are devoted to promoting the macro mechanical strength of PI nanofiber membrane by inhibiting the slippage among the fibers. Lithium polyacrylate (PAALi) is a kind of excellent binder, and it contributes to increasing the adhesion effect between the fibers. As a result, the PI nanofiber membrane treated by PAALi solution shows the mechanical strength of 16.1 MPa, higher than 5.0 MPa of pristine PI membrane. The introduction of this binder makes the originally loose and disordered PI nanofibers cross-link with each other and prevents from the slip between the fibers. Surprisingly, the PAALi binder has no effect on the thermal stability and electrochemical performance of PI nanofiber separator. Furthermore, these LiCoO2 /Li cells using the modified PI nanofiber separators exhibit better cycling stability and superior rate performance compared with the cells containing pristine PI separators. It demonstrates that the use of PAALi binder is a promising method to improve the mechanical strength of nanofiber membrane, which gets it applied in the high-power LIB. Highlights: Cross-linked PI nanofiber membrane is prepared by adding PAALi as binder. PI-0.9 separator have improved mechanical strength. LiCoO2/Li cell with PI-0.9 separator exhibits excellent battery performance.